Question Number 110471 by abdullahquwatan last updated on 29/Aug/20
$$\mathrm{the}\:\mathrm{sum}\:\mathrm{of}\:\mathrm{all}\:\mathrm{x}\:\mathrm{values} \\ $$$$\left({x}^{\mathrm{2}} −\mathrm{6}{x}+\mathrm{9}\right)^{\frac{{x}−\mathrm{3}}{{x}−\mathrm{1}}} \:=\:\left({x}−\mathrm{3}\right)^{\left({x}−\mathrm{4}\right)} \\ $$
Answered by Rasheed.Sindhi last updated on 29/Aug/20
$$\left({x}^{\mathrm{2}} −\mathrm{6}{x}+\mathrm{9}\right)^{\frac{{x}−\mathrm{3}}{{x}−\mathrm{1}}} \:=\:\left({x}−\mathrm{3}\right)^{\left({x}−\mathrm{4}\right)} \\ $$$$\left(\:\left({x}−\mathrm{3}\right)^{\mathrm{2}} \:\right)^{\frac{{x}−\mathrm{3}}{{x}−\mathrm{1}}} \:=\:\left({x}−\mathrm{3}\right)^{\left({x}−\mathrm{4}\right)} \\ $$$$\:^{\bullet\:} \frac{\mathrm{2}\left({x}−\mathrm{3}\right)}{{x}−\mathrm{1}}={x}−\mathrm{4} \\ $$$$\:\:\:\:\:\mathrm{2}{x}−\mathrm{6}={x}^{\mathrm{2}} −\mathrm{5}{x}+\mathrm{4} \\ $$$$\:\:\:\:{x}^{\mathrm{2}} −\mathrm{7}{x}+\mathrm{10}=\mathrm{0} \\ $$$$\:\:\:\left({x}−\mathrm{2}\right)\left({x}−\mathrm{5}\right)=\mathrm{0} \\ $$$$\:\:\:\:{x}=\mathrm{2}\:\vee\:{x}=\mathrm{5} \\ $$$$\:^{\bullet} {x}−\mathrm{3}=\mathrm{0},\mathrm{1}\Rightarrow{x}=\mathrm{3}\:\vee{x}=\mathrm{4} \\ $$$$\:\:{But}\:{x}=\mathrm{3}\:{produces}\:{indeterminate} \\ $$$${form}\:\mathrm{0}^{\mathrm{0}} \\ $$$${So}\:{Solution}\:{Set}\:{is} \\ $$$$\:\:\:\left\{\mathrm{2},\mathrm{4},\mathrm{5}\right\} \\ $$
Commented by abdullahquwatan last updated on 29/Aug/20
$$\mathrm{3}\:\mathrm{included}? \\ $$
Commented by Rasheed.Sindhi last updated on 29/Aug/20
$${Sorry}\:{it}'{s}\:{excluded}\:{because}\:{x}=\mathrm{3} \\ $$$${gives}\:{indeterminate}\:{form}\:\mathrm{0}^{\mathrm{0}} \\ $$
Commented by Rasheed.Sindhi last updated on 29/Aug/20
$$\mathcal{T}{hanks}\:{abdullah}\:{for} \\ $$$${mentkoning}\:{error}. \\ $$
Commented by abdullahquwatan last updated on 29/Aug/20
$$\mathrm{thank}\:\mathrm{you}\:\mathrm{sir} \\ $$